Status of the a class certified zoos and aquariums in turkey - Ahmet Selçuk Özen (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study is to determine the statues of A class certified Zoos and Aquariums in Turkey, which are playing important role in veterinary, zoology and zootechnics sciences. In addition, to suggestions to establish a contemporary institution Materials and Methods: In this study, the status of A class certified Zoos and Aquariums, established according to operational procedures and principles of the “Animal protection Law Article 22 with regulation number 5199 act” dated August 11, 2007 and published in Official Gazette with number 26610 in Turkey, were detected by observations, interviews, small number of literature and internet records. Results: It was detected that eleven Zoos and Aquariums with A class certifications were established until the date of August 6, 2014 in Turkey. The number of Zoos and Aquariums were established as four in Marmara region, three in Central Anatolia region, two in White Sea region and one each in Aegean and Southern East region of Turkey. Conclusions: It can be thought that Zoos in Turkey may have important roles in the protection of species. However, the duration time should be accelerated the transformation to contemporary Zoos